Trajetórias urbanas em pesquisas de atividade física: perspectiva centrada na vizinhança - Amanda Paula Fernandes (2018)
Introduction: promoting recreational physical activity in the daily lives of urban populations is a global challenge to health policies and requires multidisciplinary actions. In a complementary way, advancing through the neighborhood-centered perspective to include multiple sites of activity, this thesis integrates urban health and daily mobility models based on global positioning sensors (GPS). Objectives: to describe the evaluation methodology and the effect of the Programa Academia da Saude on health promotion and equity in the city of Belo Horizonte / MG, as well as to propose a method to measure the exposure to the environment built for recreational physical activity from the RECORD Multisensor study Ilê-de-France / France. Methods: This thesis integrates three distinct studies: (i) the household survey "Saúde em Beagá" (2008-2009), which had a stratified probabilistic sampling design in three-stage clusters (census tract, domicile and 18-year-old resident and more) in which n = 4,048 non-users of the program were interviewed at different distances of three poles of the Programa Academia da Saude with planned construction, and one polo in operation. (ii) The "Move-se Academias" survey (2014-2015) followed similar outline design from the baseline. The study continued cross-monitoring of another eight-pole program in the city, including n = 1376 adults and n = 402 program users. The Brazilian database included the perception of the quality of life, satisfaction with life, social life and participation in the neighborhood between users and female non-users and at least 40 years old. In addition, the non-users group was stratified into family income <3 and 3 minimum wages and compared between groups and strata (Article 1), finally, (iii) the RECORD Multisensor study (2014-2015) conducted in Paris and metropolitan region from the convenience sub-sample of the RECORD cohort. Francophone subjects, aged between 30 and 79 years, residing in the areas of a priori selected studies were eligible. For seven days they used QStarz BT-Q1000XT GPS and Actigraph GT3X + triaxial accelerometers, among other sensors. The data collected were processed and validated from automated tools and mobility surveys to identify the locations of activities, trips between such locations, modes of transportation used, nature and duration of activity performed. The database is composed of the temporal sequence of locations visited provided by n = 286 individuals, totaling 31,176 observations (Article 2). Results: the prevalence of leisure-time assets among non-users was of 30.2% and users of 53.7%. Better perception of quality of life, satisfaction with life, greater social relations and participation in the neighborhood were observed among women with higher income compared to their counterparts (p <0.001). On the contrary, users reported better perception for all validated constructs in relation to lower income pairs (Article 1). In a multidisciplinary view, time space budgets - or sequence of locations visited during individual trajectories - is critical to investigating immediate environmental determinants, capturing situational factors and circumstances of health events, investigating urban planning forecasts and solutions, and overcoming memory bias associated with selfreport measures. The RECORD Multisensor study collected accurate information on the temporal space distribution of individuals' behavior. The method proposed in this thesis (Article 2) uses the sequence of activity locations to form triads, which are composed of three successive locations. In the immediately prior and subsequent locations the exposure / accessibility features of the built environment can be measured. The middle of the triad represents the outcome (eg, place visited for physical activity), which may be a function of the spatio-temporal budget and the structural opportunities present in the previous and subsequent activity locations. The triads constitute statistical units of analysis. Conclusion: the Programa Academias da Saude has provided physical activity to the vulnerable population and seems to act on other outcomes besides lifestyle. The proposed momentary design is methodological advancement in comparison to the measures of exposure centered in the residence. The method has potential impact on physical activity and environment research. Exploring recreational physical activity in urban space, integrating areas inside and outside the neighborhoods, can contribute to understanding and coping with global physical inactivity and its iniquities.